Evaluation of the quality of life of cancer patients undergoing chemotherapy - Eliana Aparecida Carlos; José Adriano Borgato; Danielle Cristina Garbuio (Universidade Federal do Ceará, 2022)
Objective: to assess the quality of life of cancer patients undergoing chemotherapy. Methods: a cross-sectional study carried out in the chemotherapy sector with 51 patients able to answer the data collection instruments. For the analyses, we adopted the variance analysis and Student's t. Results: the health score indicated moderate quality of life and the symptoms nausea and vomiting, diarrhea, and dyspnea were the most present. The scores of the global health scale showed differences between age groups and presence of metastasis; diarrhea and financial difficulties showed differences with respect to gender; pain was more cited by those who did not undergo surgery; insomnia and nausea and vomiting were related to the time of treatment. Conclusion: participants had moderate overall health scores and the main functional levels affected by the treatment were social and emotional.